(untitled) (Web of Teachers: Inderscience Research, 2023)
In this article, the development of the sculptural art of Uzbekistan, as well as the reflection of the image of our ancestors, the symbolic and philosophical solution of the sculpture, the oldest examples of sculptural art of Uzbekistan, the monument type of sculpture dedicated to Navoi and Jami, the Sahibqiron a created in sculptural art.It is described in detail about the artistic appearance of Timur.